A new mouse mutant with a discrete mutation in Pcdhgc5 reveals that the Protocadherin γC5 isoform is not essential for dendrite arborization in the cerebral cortex - Camille M. Hanes; David M. Steffen; George C. Murray; Robert W. Burgess; Joshua A. Weiner; Andrew M. Garrett (PLoS ONE, 2026)
There are ~ 60 clustered protocadherin (cPcdh) isoforms expressed from three gene clusters ( Pcdha , Pcdhb , Pcdhg ) arrayed in tandem across nearly 1 Mb in mammals. cPcdhs are homophilic cell adhesion molecules (CAMs) critical for a host of neural developmental functions consistent with a role in cell-cell recognition. Indeed, isoforms make recognition modules in combination to generate recognition diversity far exceeding the ~ 60 individual CAMs. However, there is also growing evidence for specialized functions for specific isoforms, particularly the C-type isoforms found at the 3’ ends of the Pcdha cluster (αC1 and αC2) and at the 3’ end of the Pcdhg cluster (γC3, γC4, and γC5). We have previously described unique roles for γC3 in dendrite arborization in the cerebral cortex and neural circuit formation in the spinal cord, as well as for γC4 in neuronal survival. Here we report a new mouse mutant specifically targeting the Pcdhgc5 exon encoding γC5. Unlike the rest of the Pcdhg cluster, expression of this isoform does not begin until postnatal stages of mouse development, increasing in the second week of life, suggesting specialized roles. We found significant expression changes in gene pathways involved in synaptic activity, learning and memory, and cognition. Despite this, we saw no major disruption in the cerebral cortex in neuronal organization, survival, dendritic arborization, or synaptic protein expression in these mutants. This new model will be an important tool for future studies delineating specific functions for γC5.